Benzo-fused perylene oligomers with up to 13 linearly annulated rings - Yang, Xuan; Rominger, Frank; Mastalerz, Michael (Angewandte Chemie. International edition, 2021)
The longer acenes with more than six linearly fused six-membered rings are still fascinating chemists and physicists because of their unique photophysical properties and their high potential for organic electronics applications. Unfortunately, with increasing size (seven and more rings) these compounds rapidly lose chemical stability. Besides kinetic and chemical stabilization approaches introducing either bulky or electron-withdrawing groups or both, such systems also have been stabilized by peri-annulation. Although strictly spoken, these peri-annulated compounds are no longer real acenes, they have fascinating properties as well. Herein, we describe the first synthesis of a new series of peri-annulated acenes with up to 13 linearly fused rings, which is unprecedented till date. Furthermore, this new series contains perylene units connected through benzene rings along their [b,k]edges, responsible for unique absorption and emission properties.